Serum cholinesterases are differentially regulated in normal and dystrophin-deficient mutant mice - Durrant, Andrea R.; Tamayev, Liliya; Anglister, Lili (Frontiers in Molecular Neuroscience, 2012)
The cholinesterases, acetylcholinesterase and butyrylcholinesterase (pseudocholinesterase), are abundant in the nervous system and in other tissues. The role of acetylcholinesterase in terminating transmitter action in the peripheral and central nervous system is well understood. However, both knowledge of the function(s) of the cholinesterases in serum, and of their metabolic and endocrine regulation under normal and pathological conditions, is limited. This study investigates acetylcholinesterase and butyrylcholinesterase in sera of dystrophin-deficient mdx mutant mice, an animal model for the human Duchenne muscular dystrophy and in control healthy mice. The data show systematic and differential variations in the concentrations of both enzymes in the sera, and specific changes dictated by alteration of hormonal balance in both healthy and dystrophic mice. While acetylcholinesterase in mdx-sera is elevated, butyrylcholinesterase is markedly diminished, resulting in an overall cholinesterase decrease compared to sera of healthy controls. The androgen testosterone (T) is a negative modulator of butyrylcholinesterase, but not of acetylcholinesterase, in male mouse sera. T-removal elevated both butyrylcholinesterase activity and the butyrylcholinesterase/acetylcholinesterase ratio in mdx male sera to values resembling those in healthy control male mice. Mechanisms of regulation of the circulating cholinesterases and their impairment in the dystrophic mice are suggested, and clinical implications for diagnosis and treatment are considered.